An Extension to Basis-Hypervectors for Learning from Circular Data in Hyperdimensional Computing - Nunes, Igor; Heddes, Mike; Givargis, Tony; Nicolau, Alexandru (2023 60th ACM/IEEE Design Automation Conference (DAC), 2023)
Hyperdimensional Computing (HDC) is a computation framework based on random vector spaces, particularly useful for machine learning in resource-constrained environments. The encoding of information to the hyperspace is the most important stage in HDC. At its heart are basis-hypervectors, responsible for representing atomic information. We present a detailed study on basis-hypervectors, leading to broad contributions to HDC: 1) an improvement for level-hypervectors, used to encode real numbers; 2) a method to learn from circular data, an important type of information never before addressed in HDC. Results indicate that these contributions lead to considerably more accurate models for classification and regression.